ANALISIS PENERAPAN KESELAMATAN PELAYARAN PADA SPEEDBOAT DI ASTRA INFRA PORT EASTKAL PT PELABUHAN PENAJAM BANUA TAKA - Ardan, Muhammad Fahrizal; Zainal, Isradi (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
This study aims to determine the level of conformity and the cause of the mismatch of shipping safety implementation, namely the life-saving appliances speedboat Eastkal 01 at Astra Infra Port Eastkal PT Pelabuhan Penajam Banua Taka. This study uses a qualitative method with an observational approach that is to determine the level of conformity and the cause of the incompatibility of the application of shipping safety, namely life-saving appliances with reference to the standards used to assess life saving appliances in Eastkal 01 speedboat type of passenger ship or passenger ship determined based on SOLAS Consolidated Edition 2014, especially in part III about Life Saving Appliances and Arrangments The results of this study determine that the application of shipping safety on the Eastkal 01 speedboat at Astra Infra Eastkal Port PT Penajam Banua Taka Port based on Safety of Life at Sea (SOLAS) standards is very suitable for speedboats with a gross weight of 21 GT with a total number of passengers transported as many as 30 passengers in terms of Life Saving Appliances, namely personal life saving appliance, Visual Signal or Distress Flare, Survival Craft and Communication as well as in terms of maintenance and care for the LSA to better ensure the condition of the LSA good when used, which is done once a month and once a year for maintenance and care The results of this study determine that the application of shipping safety on the Eastkal 01 speedboat at Astra Infra Eastkal Port PT Penajam Banua Taka Port based on Safety of Life at Sea (SOLAS) standards is very suitable for speedboats with a gross weight of 21 GT with a total number of passengers transported as many as 30 passengers in terms of Life Saving Appliances, namely personal life saving appliance, Visual Signal or Distress Flare, Survival Craft and Communication as well as in terms of maintenance and care for the LSA to better ensure the condition of the LSA good when used, which is done once a month and once a year for maintenance and care. But in this study, some attributes are lacking in personal life-saving appliance, namely lifejacket light, one of the complement of lifejacket that has not been implemented and lifebuoy self-activating smoke signal for lifebuoy by regulations or Safety of Life at Sea Chapter III standards regarding life-saving appliances and arrangments and Life Saving Appliance Code in Chapter II and drill or emergency training is still not often done by Eastkal employees.